A note on foreign bank ownership and monitoring: An international comparison - Bertus, Mark; Jahera, John S.; Yost, Keven (Journal of Banking & Finance, 2008)
This paper empirically analyzes the relation between foreign bank ownership and the three pillars of the New Basel Capital Accord (i.e., capital regulatory oversight, supervisory oversight, and market discipline). Using a new database covering 153 countries, we find that countries with greater market discipline have a lower presence of foreign banks operating in their economy. Furthermore, our evidence indicates that capital regulatory oversight and supervisory oversight are not significantly related to foreign bank ownership.